2014
DOI: 10.4093/dmj.2014.38.1.13
|View full text |Cite
|
Sign up to set email alerts
|

The Hijacking of Cellular Signaling and the Diabetes Epidemic: Mechanisms of Environmental Disruption of Insulin Action and Glucose Homeostasis

Abstract: The burgeoning epidemic of metabolic disease causes significant societal and individual morbidity and threatens the stability of health care systems around the globe. Efforts to understand the factors that contribute to metabolic derangements are critical for reversing these troubling trends. While excess caloric consumption and physical inactivity superimposed on a susceptible genetic background are central drivers of this crisis, these factors alone fail to fully account for the magnitude and rapidity with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 99 publications
(137 reference statements)
0
35
1
3
Order By: Relevance
“…Supporting these warnings are, among others, several epidemiological and in vivo studies that reported the positive correlation of EDCs concentrations, both in AT and plasma, with the prevalence of obesity, MetS, insulin resistance, hypertension and CVD 2123 , as well as adipocyte dysfunction 24 .…”
Section: Introductionmentioning
confidence: 83%
“…Supporting these warnings are, among others, several epidemiological and in vivo studies that reported the positive correlation of EDCs concentrations, both in AT and plasma, with the prevalence of obesity, MetS, insulin resistance, hypertension and CVD 2123 , as well as adipocyte dysfunction 24 .…”
Section: Introductionmentioning
confidence: 83%
“…Sua complexidade associada à elevada incidência e prevalência concorrem para que essa doença seja considerada um importante problema de saúde pública (2) .…”
Section: Introductionunclassified
“…O pé diabético ocorre quando uma área lesionada ou infeccionada nos pés desenvolve úlcera (5) . Acomete cerca de 15% dos pacientes com DM ao longo da vida e é responsável por mais de 60% das amputações não traumáticas (1)(2) , o que consequentemente gera ampla repercussão social e econômica (6) .…”
Section: Introductionunclassified
“…Another potentially productive research area in b-cell failure is the various interactions of b-cell function with environmental factors (e.g., endocrine disruptors such as arsenic), as well as genetic and epigenetic factors. This is especially relevant to the task of solving the evolving diabetes epidemic in developing countries [6]. Due to the development of new techniques and our understanding of b-cell biology, the research areas included in these three themes represent numerous and increasing opportunities for investigators, both established and new, to develop novel diabetes therapies.…”
mentioning
confidence: 99%